Preparation of Multifunctional N-Doped Carbon Quantum Dots from Citrus clementina Peel: Investigating Targeted Pharmacological Activities and the Potential Application for Fe3+ Sensing - Silvija Šafranko; Anamarija Stanković; Sugato Hajra; Hoe-Joon Kim; Ivica Strelec; Maja Dutour-Sikirić; Igor Weber; Maja Herak Bosnar; Petra Grbčić; Sandra Kraljević Pavelić; Aleksandar Széchenyi; Yogendra Kumar Mishra; et al. (MDPI AG, 2021)
Carbon quantum dots (CQDs) have recently emerged as innovative theranostic nanomaterials, enabling fast and effective diagnosis and treatment. In this study, a facile hydrothermal approach for N-doped biomass-derived CQDs preparation from Citrus clementina peel and amino acids glycine (Gly) and arginine (Arg) has been presented. The gradual increase in the N-dopant (amino acids) nitrogen content increased the quantum yield of synthesized CQDs. The prepared CQDs exhibited good biocompatibility, stability in aqueous, and high ionic strength media, similar optical properties, while differences were observed regarding the structural and chemical diversity, and biological and antioxidant activity. The antiproliferative effect of CQD@Gly against pancreatic cancer cell lines (CFPAC-1) was observed. At the same time, CQD@Arg has demonstrated the highest quantum yield and antioxidant activity by DPPH scavenging radical method of 81.39 ± 0.39% and has been further used for the ion sensing and cellular imaging of cancer cells. The obtained results have demonstrated selective response toward Fe3+ detection, with linear response ranging from 7.0 µmol dm−3 to 50.0 µmol dm−3 with R2 = 0.9931 and limit of detection (LOD) of 4.57 ± 0.27 µmol dm−3. This research could be a good example of sustainable biomass waste utilization with potential for biomedical analysis and ion sensing applications.